Discontinuation of Postoperative Prophylactic Antibiotics After Noninstrumented Spinal Surgery: Results of a Quality Improvement Project. (July 2018) - Lewis, Ariane; Lin, Jessica; James, Herbert; Hill, Travis C.; Sen, Rajeev; Pacione, Donato
Background: Numerous medical society guidelines recommend discontinuation of antibiotics at a maximum of 24 hours after noninstrumented spinal surgery, even when a drain is left in place. As a result of these recommendations, our institution's Neurosurgery Quality Improvement Committee decided to stop administering prolonged prophylactic systemic antibiotics (PPSAs) to patients with drains after noninstrumented spinal surgery. Methods: We retrospectively reviewed data for patients who had noninstrumented spinal surgery performed by a neurosurgeon at our institution between December 2012 and July 2014 (PPSA period) and December 2014 and July 2016 (non-PPSA period) and had a drain left in place postoperatively. In the PPSA period, patients received antibiotics until drain removal. In the non-PPSA period, patients received antibiotics for a maximum of 24 hours. Results: We identified 58 patients in the PPSA period and 55 in the non-PPSA period. Discontinuation of PPSAs resulted in a nonsignificant increase in the frequency of surgical site infections (SSIs; 0% in the PPSA period vs 4% in the non-PPSA period; P = .24). Conclusion: After discontinuing PPSAs for patients with noninstrumented spinal procedures, as is recommended for quality improvement, we saw a nonsignificant increase in our rate of SSIs. Further monitoring of this population is warranted.